Pencegahan Bullyiang dan Pelecehan Seksual di Dunia Pendidikan Melalui Sosialisasi di Madrasah Ulumul Qur’an - Masthura, Natasya; Hayati, Vivi; Hasmiyati, Cut; Yuana, Adella (Universitas Teuku Umar, 2025)
This community service activity was carried out at Madrasah Ulumul Qur’an with the aim of providing students with an understanding of the importance of preventing bullying and sexual harassment. The materials presented covered the basic concepts of bullying and sexual harassment, their causes, and the impact on victims and the educational environment. The results of the activity showed that the students were able to understand how to prevent bullying and sexual harassment. Prevention efforts are crucial and were promoted through legal literacy and socialization during this activity to help reduce the number of bullying and sexual harassment cases in educational settings. The activity was conducted through presentations and discussions, accompanied by case studies and problem-solving strategies related to bullying and sexual harassment experienced by madrasah students. This initiative is expected to serve as an initial step in fostering awareness among students to enhance their understanding of bullying and sexual harassment, as well as the values of Islamic teachings in daily life.